CREATING A CORPORATE CULTURE TO ENHANCE PRODUCTIVITY AT PT DIRGANTARA INDONESIA (PERSERO) - Kusmayadi, Heri
PT Dirgantara Indonesia (PTDI), has been capable in producing and selling the aircrafts, helicopters, weapon system, missile, dan maintenance to other countries. Shortly, PTDI has become one of big companies in Asia Pacific, specializing in medium and lighter aircrafts manufacturing and business. PTDI even recently leads in engineering services, but PTDI had ever have traumatic and lesson-leart type of experiences in the year of 1998 to 2004, up and down growth including employee downsizing. After that, PTDI can get rid of the crisis condition, and starts to rise a leading company in aircraft business in some regions, making some collaborations with other big aircraft companies, and succeed in buiding a new medium type aircraft N219 although potential aircraft such as CN235, N212 and some helicopter remains to be the source of revenue. However in other side, the PTDI has not yet owned corporate culture containing belief, value, and behavior as the guidance for the employee how they work around here in achieving the target. The unavalaibility of corporate culture in this company has been impacting to employee disobedience to human resource regulation and procedure in which work hour indiscipline become a big issue, increasing of rejection tag level; and work performance (productivity) declining. Therefore, to enhance the productivity leading to high performance, the company must fulfil one of requirements i.e creating corporate culture containing beliefs, value and behavior standard as the guidance for employee. Before creating new corporate culture, an analysis has been conducted to see the recent potention in business by using SWOT Analysis to analyze PTDI from the aspects of Strength, Weaknesses, Opportunity and Threat in relating the importance of corporate culture implementation, and Questionnaire Analysis by doing data collecting and data analyzing based on quistionnaire distributed and collected from employee. In data analysing, it has been carried out potraiting to find out existing value (das Sein) and expected value (das Sollen), and their gap. By using the value gap, emmmerging unrequired value (negative values) and new and old expected value that become operating value, primary value and core value as the source of new corporate culture creation. With new corporate culture, it is expected to have new culture tranformation that impact to performance increasing, so that need to be arranged how the new corporate culture is implemented and internalized gradually. At the end the corporate culture will embody to the way employee think, work and behave in achieving the target of the company